Application of modified eddy dissipation concept with large eddy simulation for numerical investigation of internal combustion engines. (10th March 2015) - Nassiri Toosi, Ali; Farokhi, Mohammadreza; Mashadi, Behrooz
Highlights: We modify EDC for using in LES of premixed flame of burner and IC engine. Standard and dynamic SGS viscosity with EDC and EDM models are compared. Flame propagation, fuel consumption and heat released energy are investigated. Using EDC, most sensitive improvements are achieved in standard Smagorinsky model. Dynamic models show significant similarity in flame propagation. Abstract: Computational methodology of large eddy simulation (LES) is tested in a real internal combustion engine geometry. Premixed turbulent combustion and the behavior of flame propagation are studied and compared with different LES and combustion process models. KIVA-3V, an open source Fortran code, is modified to implement large-eddy simulation technique based on one-equation sub-grid scale (SGS) turbulent kinetic energy and Smagorinsky models. For combustion process, improved turbulent-mixing combustion models based on eddy-dissipation model (EDM) and modified eddy-dissipation concept (EDC) are implemented and studied in case of using LES. The models with modified combustion processes of EDM and EDC are validated using experimental data of premixed combustion of laboratory burner with application of converging optimum and desired combustion model constants. Also experimental in-cylinder pressure data are used to validate the numerical CFD results of engine geometry. The physics of flow structure, flame propagation, heat energy released and fuel mass consumption during combustion are studied and compared by LES models. It is observed that large-scale of unsteady turbulent flow motions are developed before spark ignition that makes different behavior of flame front shape in combustion process with different turbulent models. Also numerical simulations indicate that different LES turbulence models may not capture the same flame propagation structure, whereas LES dynamic SGS viscosity models in comparison with standard constant models, almost capture the same flame front shape and propagation structure in the combustion chamber.